Effects of dl-3-n-butylphthalide on production of TXB2 and 6-keto-PGF1 alpha in rat brain during focal cerebral ischemia and reperfusion - Chong Zhao-Zhong; Feng Yi-Pu (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of dl-3-n-butylphthalide (NBP) on the changes of thromboxane B2 (TXB2) and 6-keto-PGF1 alpha (6-keto-PGF1 alpha) contents in hippocampus, striatum, and cerebral cortex of rats subjected to focal cerebral ischemia followed by reperfusion. METHODS: Focal cerebral ischemia was induced by inserting a nylon suture into intracranial segment of internal carotid artery from external carotid artery and blockade of the origin of middle cerebral artery. For reperfusion, the suture was pulled out to restore the blood flow to the ischemic brain. Determination of TXB2 and 6-keto-PGF1 alpha was performed by RIA method. RESULTS: Reperfusion following focal cerebral ischemia resulted in increases in TXB2 at 5 min and 6-keto-PGF1 alpha at 30 min and a decrease in the ratio of epoprostenol (PGI2)/thromboxane A2 (TXA2) (6-keto-PGF1 alpha/TXB2) at 5 min in hippocampus, striatum, and cerebral cortex. NBP 10 mg.kg-1 reduced the content of TXB2 without decreasing effect on 6-keto-PGF1 alpha. NBP 20 mg.kg-1 reduced both TXB2 and 6-keto-PGF1 alpha in lesser extent than aspirin (Asp, 20 mg.kg-1). NBP 20 or 10 mg.kg-1 elevated the ratio of PGI2/TXA2 after reperfusion, but Asp 20 mg.kg-1 did not increase the ratio except in striatum at 5 min after reperfusion. CONCLUSION: NBP increases the ratio of PGI2/TXA2 which may have beneficial effects on the impaired microcirculation in postischemic brain tissues.